2019
DOI: 10.1017/s0950268819001493
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation throughout pregnancy and fetal growth restriction in rural Nepal

Abstract: Maternal systemic inflammation during pregnancy may restrict embryo−fetal growth, but the extent of this effect remains poorly established in undernourished populations. In a cohort of 653 maternal−newborn dyads participating in a multi-armed, micronutrient supplementation trial in southern Nepal, we investigated associations between maternal inflammation, assessed by serum α1-acid glycoprotein and C-reactive protein, in the first and third trimesters of pregnancy, and newborn weight, length and head and chest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 38 publications
(52 reference statements)
0
14
1
Order By: Relevance
“…Maternal undernutrition during pregnancy causes metabolic stresses which may adversely impact on fetal growth and birth outcomes. In this study and others, underweight women were found more likely to have an LBW or SGA infant compared to women with a normal weight [48][49][50][51]. Furthermore, our results show that although maternal nutritional supplementation with a lipid-based supplement (PE or PE + MMN) during pregnancy was associated with altered lipid levels, no direct associations were observed between maternal supplement groups and birth weight outcomes.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…Maternal undernutrition during pregnancy causes metabolic stresses which may adversely impact on fetal growth and birth outcomes. In this study and others, underweight women were found more likely to have an LBW or SGA infant compared to women with a normal weight [48][49][50][51]. Furthermore, our results show that although maternal nutritional supplementation with a lipid-based supplement (PE or PE + MMN) during pregnancy was associated with altered lipid levels, no direct associations were observed between maternal supplement groups and birth weight outcomes.…”
Section: Discussioncontrasting
confidence: 46%
“…HDL) during this phase may cause lipid obstruction of vascular tissues and inflammation resulting in a cascade of events leading to LBW. Maternal inflammation during pregnancy has been associated with IUGR in a study conducted in rural Nepal (n = 653) [49] and with lower birth weight in a cohort (n = 144) from Tanzania [50]. In contrast, the pathophysiological mechanisms associated with the risk of SGA may appear later in pregnancy; during the catabolic phase where insulin resistance and placental hormones induce the release of free fatty acids from maternal adipose tissue to meet the heightened fetal energy demands.…”
Section: Discussionmentioning
confidence: 99%
“…Overall malaria burden is high with 403 cases per 1,000 in 2016 and annual incidence increasing since 2012 [20]. Maternal systemic inflammation during pregnancy has been associated with diverse adverse outcomes including fetal growth restriction, and preterm birth [1,21,22], but little is known about its association with maternal leukocyte telomere length, particularly in SSA, where malnutrition and infection during pregnancy are more common than North American or European contexts.…”
Section: Nutrition and Infection In Pregnancymentioning
confidence: 99%
“…CRP levels rise sharply during the early phase of an infection, whereas AGP levels gradually increase so timing of testing may be critical to assess levels [62]. Furthermore, other studies were not conducted with pregnant women and CRP levels increase and AGP decrease with duration of gestation [21]. As such, the interplay between inflammatory status and leukocyte telomere length may not be fully understood in the context of pregnancy.…”
Section: Infections and Inflammationmentioning
confidence: 99%
“…The placenta acts as the primary interface between mother and fetus, allowing nutrient and oxygen transfer which supports fetal growth and development. Obesity-associated maternal-fetal inflammation contribute to various adverse pregnancy outcomes including placental dysfunction (16, 17), preeclampsia, neurodevelopment (18), intrauterine growth restriction (19, 20), and preterm labor (21, 22). An investigation of the chronic pro-inflammatory milieu in placentas from obese pregnancies showed a two-to three-fold increase in resident macrophages (CD68+ and CD14+) and expression of pro-inflammatory cytokines compared with placentas from lean pregnancies (23).…”
Section: Introductionmentioning
confidence: 99%